The Effect of Curing Time and Extraction Temperature on the Quality of Gelatin Produced from Cattle Hide - Triatmojo, Suharjono (UB Press, 2010)
The experiment was conducted to examine the effect of time curing and extraction temperature on gelatin quality. Gelatin was produced from wet slated cattle hide. The hide was cut in 10 x 10 cm and was then continued by curing at room temperature. The time of curing lasted for 1, 2 and 3 weeks. After curing, the hide was washed in flowing water for 12 hours, then acidified in 0.1 M Sulfuric acid for 4 hours, to remove the line. Hide containing free lime was extracted at different temperature (50 C, 60 C and 70 C) for 6 hours. The volume of each fraction was recorded. The sample was taken for determining the quantity of extractable gelatin, including gel strength, viscosity, dry matter, protein, fat and ash content. Gelatin was filtered with free fat filter paper then dried at 60 to 70 C for 12 hours, which finally formed film. The film was weighed and ground to produce gelatin powder. The results showed that time of curing and extraction temperature did not affect gel strength, viscosity and chemical composition of gelatin, except for protein content. The higher temperature of extraction the more extrcatable gelatin produced. Curing for one week at 23-30 C followed by extraction at 50 C for 6 hours produced the best gelatin quality. Gelatin can be produced by extraction at 50-70 C.